The archaeology of small-scale slavery in antebellum Missouri - Haas, James Elliott, author; Van Buren, Mary, advisor; LaBelle, Jason, committee member; Knowles, Katie, committee member (Colorado State University. Libraries, 2019)
In this thesis, I examine small-scale slavery and resistance by the enslaved to their condition using the conceptual framework of resistant accommodation, as applied to the circumstances on my family's farm in Missouri. My family were slaveholders who came from Kentucky and settled in Hardin Township, Clinton County, Missouri, circa 1833. Family oral history included information on the location of the first house, but little else. The term resistant accommodation, developed based on small-scale farming operations in colonial New England, implies that the enslaved outwardly conformed to the demands of their enslavers while covertly circumventing those demands to further their own interests. In this conceptual framework, resistance is not an end in itself. It further suggests that individual acts of resistance coalesced into a community of resistance through the networking, shared experiences, and mutual trust that developed among the enslaved when they were able to exploit gaps in the surveillance of their enslavers. Gaps in surveillance arose in part from enslavers' competing attempts to maintain surveillance while also using their work force efficiently and emphasizing separateness through the control of shared space. The nature of the landscape was also a factor. I hypothesize that conditions in colonial New England were broad enough to apply to slaveholder surveillance and resistance by the enslaved on small-scale farms across the antebellum Upper South and in Border States such a Missouri. I then present a case study using data from my family farm, settled by my great-great-great grandfather James Elliott, to test whether those data support an interpretation that conditions for the people my family enslaved were consistent with the expectations of resistance accommodation. The Euroamerican settlers of the Upper South were largely small-scale yeoman farmers with smaller acreages and few or no slaves, interspersed physically with a smaller number of large-scale planters with large acreages and many slaves. Conditions and opportunities for the enslaved differed between small-scale and large-scale operations in terms of labor management, housing, and degree of surveillance. To understand the opportunities available to the people my family enslaved, it was important to determine the scale of their farming and slaveholding operation, and the nature of the surrounding landscape, for which I used both archaeological and historical methods. The archaeological investigations included remote sensing and exploratory excavation at the site family oral history indicated was the location of the first house, followed by artifact analysis. The results suggest that a two-room hewn log house on a limestone foundation, typical of the antebellum period, existed on the site. The artifacts support an antebellum origin for the house, and the presence of male and female occupants, but provide no unique markers of African American occupancy. A comparison of the type, number, and quality of artifacts with those from a well-documented large-scale slaveholding operation suggest that the Elliott family had a small-scale operation. Historical records confirmed that James Elliott was a small-scale farmer and slaveholder who raised a typical suite of crops and livestock that was sufficient to support his family and labor force while providing surplus production for the commercial market. Culturally, James and his family and slaves lived in an agrarian society. Only about 29 percent of Hardin Township's heads of household were slaveholders, but the society was highly stratified based on land and slave ownership, with greater wealth accruing to six large-scale slaveholders. In a small-scale farming operation, the Elliotts' enslaved (and those of other small-scale holders) could expect reduced surveillance while working, running approved errands, and attending church. These moments likely afforded the enslaved some time to further their own interests and socialize with their peers. The housing practices of small-scale holders were variable; James was among the 41 percent of them who did not provide separate slave quarters, making unauthorized nighttime excursions more difficult. I used a viewshed analysis to examine the characteristics of physical landscape; this analysis revealed that extensive areas around the Elliott farm were out of sight of the Elliott log house and the houses of neighboring slaveholders, and that the riparian corridors of small creeks connected these areas in ways that would allow slaves to gather clandestinely while avoiding detection. There is, therefore, compelling circumstantial evidence that opportunities were available to the enslaved to reduce or avoid surveillance. In addition, a report by the Hardin Township Slave Patrol from December 1859 shows that African Americans were in fact availing themselves of these opportunities, meeting in groups of two to six without authorization. These group actions show that a community of resistance existed among the township's enslaved, a community built upon individual acts of resistance. It is likely that similar conditions prevailed throughout the Upper South.
Keywords: Missouri; surveillance; yeomen; resistance; accommodation; viewshed